1998
DOI: 10.1021/la980408y
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Preformed 3D Nuclei in Langmuir Monolayers below Critical Supersaturation

Abstract: The features of the nucleation−growth process during the transformation of two-dimensional monolayer material into three-dimensional nuclei in supersaturated Langmuir monolayers of stearic acid are studied by a double surface pressure step technique. The first surface pressure step to a surface pressure π above the critical surface pressure (π > πcrit) leads to the formation of 3D nuclei according to a progressive nucleation process. 3D nuclei preformed at different surface pressures under the condition π > πc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…Besides monolayer fracture, also a thermodynamically driven expulsion of the interfacial molecules can take place. Examples hereof are the formation of a 3D solid phase [13], [14] or the (compression- 50 induced) dissolution of interfacial species into the sub-phase [13,15,16]. The occurrence of these processes makes the resistance of the layer against loss of its constituents an important aspect of its mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides monolayer fracture, also a thermodynamically driven expulsion of the interfacial molecules can take place. Examples hereof are the formation of a 3D solid phase [13], [14] or the (compression- 50 induced) dissolution of interfacial species into the sub-phase [13,15,16]. The occurrence of these processes makes the resistance of the layer against loss of its constituents an important aspect of its mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism in which 3D crystals nucleate and grow in a direction perpendicular to the interface [17] has been proposed by Xu et al [18] and Carry and Rideal [19], demonstrated by Lee and Liu [13] and modeled by Vollhardt et al [20]. Nucleation can only occur if the 55 surface pressure exceeds the equilibrium spreading pressure (ESP) [14,18]. Similar to the situation in bulk liquids, it involves an activation energy which diminishes upon increasing the surface pressure [21].…”
Section: Introductionmentioning
confidence: 99%
“…Vollhardt et al [58,[71][72][73] proposed the most widely used kinetic models of the collapse. These models were based on the kinetic dependences of the area of a monolayer relaxing to the stable state upon the collapse at a constant value of Π > Π lim .…”
Section: Metastability and Nonequilibrium Structures In Langmuir Monomentioning
confidence: 99%
“…13 One reason for the appearance of the overshoot is because the nucleation process is, in any case, slower than the monolayer compression rate. 13 One reason for the appearance of the overshoot is because the nucleation process is, in any case, slower than the monolayer compression rate.…”
Section: Surface Pressurearea Isothermmentioning
confidence: 99%